KOLABORASI DINAS PENDIDIKAN, SEKOLAH DAN WALI MURID DALAM PROSES BELAJAR MENGAJAR DARI RUMAH TINGKAT PENDIDIKAN DASAR DI KOTA PEKANBARU PADA MASA PANDEMI COVID-19 TAHUN 2020 - Risya Nofriani; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The teaching and learning process must still take place even in the emergency conditions of the Covid-19 pandemic. This is related to the fulfillment of the right of students to obtain basic education services as stated in the 1945 Constitution. The Learn from home policy is closely related to the use of technology. The implementation of the learning from home policy requires the collaboration of the Education Office, schools and parents so that students can get excellent educational services. This study aims to explain the collaboration that occurs between the Pekanbaru City Education Office, schools and parents in the teaching and learning process from home during the Covid-19 pandemic. The theory used in this study is based on 3 stages of the collaboration process according to Gray, namely problem determination, goal setting, and implementation. The research method used in this research is a qualitative research method. Data collection techniques through interviews, and documentation studies from various sources. The results of this study show the collaboration of the Education Office, schools and parents in the process of teaching and learning from home at the basic education level in Pekanbaru City during the Covid-19 pandemic in 2020 in the process of determining the problem, there were limited learning support facilities and lack of ability to operate learning support facilities from home. In the process of goal setting is that educational services must still run. The implementation has not gone well because it is constrained by the lack of awareness of the role of parents in the collaboration that occurs and limited costs. Keywords: Collaboration, Learning From Home, Elementary School